EXPERIMENTAL INVESTIGATIONS OF PIPELINE FILLING AND EMPTYING IN A SMALL-SCALE APPARATUS - Uroš Karadžić; Anton Bergant (Journal of Energy Technology, 2024)
This paper serves as a reference for further investigations of pipeline filling and emptying in a relatively small-scale pipeline apparatus. The apparatus consists of an upstream end high-pressurized tank, horizontal steel pipeline, four valve units positioned along the pipeline including the end- points, and a downstream end tank. The filling of an initially empty pipeline is performed by a sudden opening of the valve positioned at the high-pressurized tank filled with water. The pipeline- emptying process is accomplished by high-pressurized air supplied from the air reservoir installed at the high-pressurized tank. The high-pressurized tank is closed, and the downstream end valve is opened. Experimental results indicate that pressure fluctuations are larger for pipeline filling in comparison to pipeline emptying. It is shown that a piezoelectric transducer with a fixed relatively low discharge time constant is not entirely appropriate for accurate low-frequency pressure mea- surements.